Pengaruh Gaya Kepemimpinan Dan Loyalitas Terhadap Tingkat Turnover Karyawan Bagian Medical Representative PT Mersifarma Malang - Rangga Dio Maydano Wicaksono; Abdul Kodir Djaelani; M. Khoirul Anwarudin Broto Suharto (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract Companies with good management should realize that the nature of employees as human beings has needs to be fulfilled. From the desire to meet basic needs, to the effort to meet secondary needs. Lack of attention to the needs and desires of employees will have a bad impact on the company itself so that it will result in the level of employee loyalty decreasing. If a manager is wrong in determining the leadership style for his employees, it will have an impact on decreasing employee loyalty, this will affect the growth of Turnover Intention in a company. Pharmaceutical companies in general will experience a condition where the employee turnover in the Medical Representative section is very large, so the researchers chose PT Mersifarma Malang branch Keywords: Leadership Style, Loyalty, Turnover Rate.